Calorimetry in Particle Physics 2003
DOI: 10.1142/9789812704894_0032
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Opal Si-W Luminometer at Lep I-Ii

Abstract: A pair of compact Silicon-Tungsten calorimeters was operated in the OPAL experiment at LEP to measure the integrated luminosity from detection of Bhabha e ± scattered at small angles from the beam line. The performance of the detector at both LEP-I and LEP-II is reviewed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 1 publication
6
69
0
Order By: Relevance
“…Within errors, the full NLO calculation can describe the ZEUS data without any intrinsic ͗k T ͘ effects. The production of direct photons and jets in direct, single-, and double-resolved photon-photon collisions has also recently been calculated in next-to-leading order (Fontannaz, Guillet, and Heinrich, 2002), and good agreement with preliminary OPAL data (Abbiendi et al, 2001d) was found. In the future, NLO calculations should be performed for the production of two photons and photons in association with light and heavy hadrons in order to obtain more information about the flavor content of photons and protons.…”
Section: Photons and Jetssupporting
confidence: 61%
“…Within errors, the full NLO calculation can describe the ZEUS data without any intrinsic ͗k T ͘ effects. The production of direct photons and jets in direct, single-, and double-resolved photon-photon collisions has also recently been calculated in next-to-leading order (Fontannaz, Guillet, and Heinrich, 2002), and good agreement with preliminary OPAL data (Abbiendi et al, 2001d) was found. In the future, NLO calculations should be performed for the production of two photons and photons in association with light and heavy hadrons in order to obtain more information about the flavor content of photons and protons.…”
Section: Photons and Jetssupporting
confidence: 61%
“…The data is not published yet and will therefore not be considered in this presentation. The OPAL data used in this analysis was obtained by G. Abbiendi et al, members of the OPAL collaboration, at center-of-mass energy near the Z 0 peak of 91.5 GeV/c 2 [16].…”
Section: Datamentioning
confidence: 99%
“…Its width is given by the total decay width of the W boson and the detector resolution. These distributions are analysed by the four LEP experiments in order to extract the pole mass and total decay width of the W boson [161,162,163,164], where a definition of mass and width using a Breit-Wigner with s-dependent width is used. The results of the experiments for the different channels and their combinations [156] are compared in Figures 1.39 and 1.40.…”
Section: Determination Of W-boson Mass and Widthmentioning
confidence: 99%